Robust hybrid decentralized controller design for Voice Coil Actuator-Fast Steering Mirror system in high-precision optical measurements - Liu, Jiabin; Li, Decheng; Chen, Hui (Measurement : journal of the International Measurement Confederation, 2026)
The Voice Coil Actuator-Fast Steering Mirror (VCA-FSM) is of significant value in high-precision optical measurement applications. However, the complex internal coupling within the system often results in inadequate multi-axis collaborative control accuracy and stability. To overcome the inherent limitations of traditional centralized control architectures in complex system information processing and multi-axis coordination, this study proposes a robust H∞–μ hybrid decentralized control framework that systematically integrates μ-synthesis and robust H∞ control methodologies. First, a preliminary robust centralized controller is designed by synergistically combining μ-synthesis and robust control techniques, iteratively incorporating enhanced system information through progressive integration. Next, variable pairing analysis is employed to systematically quantify interaction intensities, thereby enabling the optimal configuration of the decentralized control structure. Finally, a decentralized controller is developed using weighted model approximation techniques to preserve critical system dynamics. The experimental results demonstrate that the proposed control strategy ensures good global performance while exhibiting enhanced robustness. Compared to traditional centralized control methods, the proposed approach reduces the repeatability positioning error of the VCA-FSM system to less than 0.9′′, achieves steady-state static resolution errors of less than 0.1 μrad on the X/Y axes, shortens the rise time by an average of 12 ms, reduces the overshoot by an average of 3.51%, enhances disturbance rejection capability by approximately 9.15%, and improves noise reduction performance by approximately 15%. •Propose a robust hybrid decentralized control method for VCA-FSM in optical measurement.•HIIA-based variable pairing method determines optimal decentralized control structure.•Global performance optimization of robust decentralized controller via Bayesian Algorithm.•Measurement system achieves ≤0.9′′ positioning error and <0.1 μrad static resolution.•Proposed strategy enhances disturbance rejection by 9.15% and noise reduction by 15%.